The International Trans-avantgarde Trans Avantgarde International. - Bonito Oliva, Achille; Argan, Giulio Carlo; Mats, B.; Barzel, Amnon; Beaton, Alexandra; Bex, Florent; Boué, Marie; Cherubini, Laura; Curiger, Bice; Glusberg, Jorge; Medved, Andrej; Moure, Gloria; et al. (Milano : Giancarlo Politi Editore Milano, 1982)
Africano, Nicholas ; Alberola, Jean-Michel ; Allen, Davida ; Anzinger, Siegfried ; Arowetti, Batia ; Art & Language ; Barcelo, Miguel ; Baselitz, Georg ; Basquiat, Jean-Michel ; Bernard, Emerik ; Berti, Duccio ; Beuys, Joseph ; Blais, Jean-Charles ; Blanchard, Rèmy ; Bohatsch, Erwin ; Boisrond, François ; Book, Max M. ; Borofsky, Jonathan ; Broto, José Manuel ; Bueno, Rafael ; Burton, Scott ; Cahn, Miriam ; Canova, Alessandro Perelli ; Cantalupo, Maria Patrizia ; Carrà, Carlo ; Casariego, Florencio Mendez ; Castelli, Luciano ; Castilla, Americo ; Ceccobelli, Bruno ; Chagall, Marc ; Chia, Sandro ; De Chirico, Giorgio ; Christmann, Gunter ; Clemente, Francesco ; Collins, James ; Combas, Robert ; Cooper, Eileen ; Cucchi, Enzo ; Dahn, Walter ; Daniels, René ; Dessi, Gianni ; Dimitrijevic, Braco ; Disler, Martin ; Dokoupil, Jiri Georg ; Dragomirescu, Radu ; Eklundh, Claes ; Elander, Kristina ; Eric, Milan ; Esposito, Enzo ; Ferrat, Dominique ; Ferrer, Raphael ; Fetting, Rainer ; Fio, Zvjezdana ; Fischli & Weiss ; Fotuna, Pietro ; Fouchain, Jérome ; Frank, Dale ; Freymuth, Alphons ; Frisch, Erich ; García Sevilla, Ferran ; Garouste, Gérard ; General Idea ; Germana, Mimmo ; Gershuni, Moshe ; Getter, Tamar ; Geva, Tsibi ; Gilbert & George ; van Gogh, Vincent ; Goldstein, Jack ; Golub, Leon ; Graf, Kowanz ; Grau, Xavier ; Guston, Philip ; Hacker, Dieter ; Haks, Janusz ; Hödicke, Karl Horst ; van Hoek, Hans ; Holstein, Pieter ; Hunter, Alexis ; Immendorff, Jörg ; Ivancic, Nina ; Jenney, Neil ; Kandinsky, Wassily ; Kern, Joseph ; Kiefer, Anselm ; Kiff, Ken ; Kirchner, Ernst Ludwig ; Kirkeby, Per ; Klein, Robert ; Klinkan, Alfred ; Klomp, Rudy ; Koberling, Bernd ; Kokoschka, Oskar ; Kozzi, Kim ; Krasover, Metka ; Kuitca, Guillermo ; Kushner, Robert ; etc.
Duits
Engels
Frans
Italiaans
Servo-Kroatisch
Nederlands